Characterization of CD4+ T Cell Subsets in Patients with Abdominal Aortic Aneurysms - Fábio Haach Téo; Rômulo Tadeu Dias de Oliveira; Liana Villarejos; Ronei Luciano Mamoni; Albina Altemani; Fabio Husemann Menezes; Maria Heloisa Souza Lima Blotta (Mediators of Inflammation)
Background. The mediators produced by CD4+ T lymphocytes are involved in the pathogenesis of aneurysmal lesions in abdominal aortic aneurysm (AAA) patients. The aim of this study was to identify and characterize the CD4+ T cell subsets involved in human AAA. Methods. The CD4+ T cell subsets in 30 human aneurysmal lesions were determined using flow cytometry (FC) and immunohistochemistry (IHC). The peripheral blood mononuclear cells (PBMCs) from patients with AAA were also analyzed by FC and compared with control subjects. Results. Human aneurysmal lesions contained IFN-γ, IL-12p35, IL-4, IL-23p19, IL-17R, and IL-22 positive cells. PBMCs from AAA patients had higher expression levels of IFN-γ, TNF-α, IL-4, and IL-22 when compared to controls. Conclusions. Our results show the presence of TH1, TH2, TH17, and TH22 subsets in aneurysmal lesions of AAA patients and suggest that these cells may be mainly activated in situ, where they can induce tissue degradation and contribute to the pathogenesis of AAA.